1996
DOI: 10.1182/blood.v87.11.4903.bloodjournal87114903
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of allogeneic CD34+ blood cells

Abstract: Pluripotent stem cells of hematopoiesis and lymphopoiesis are among the CD34+ cells in blood or bone marrow. After granulocyte-colony stimulating factor (G-CSF) treatment, 1% to 2% of the mononuclear cells in blood are CD34+ cells, which can be procured by leukapheresis. We investigated the potential of CD34+ blood cells for reconstituting hematopoiesis and lymphopoiesis after allogeneic transplantation. HLA- identical sibling donors of 10 patients with hematologic malignancies were treated with G-CSF (filgras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(42 citation statements)
references
References 36 publications
3
37
0
2
Order By: Relevance
“…Several series of CD34 þ selected PBPC have now been published (Link et al, 1996;Bensinger et al, 1996a;Urbano-Ispizua et al, 1997). Two studies (Link et al, 1996;Bensinger et al, 1996a) reported a high incidence of severe (grade II-IV) acute GVHD (60-80%) in patients receiving a CD3 þ cell dose of approximately 1 × 10 6 /kg when post-transplant cyclosporin alone was used for GVHD prophylaxis. Urbano-Ispizua et al (1997) recently updated the Spanish experience in 20 patients undergoing CD34 þ selected PBSC using CSA combined with prednisolone post-transplant.…”
Section: Clinical Results Of Pbpc Transplantsmentioning
confidence: 99%
“…Several series of CD34 þ selected PBPC have now been published (Link et al, 1996;Bensinger et al, 1996a;Urbano-Ispizua et al, 1997). Two studies (Link et al, 1996;Bensinger et al, 1996a) reported a high incidence of severe (grade II-IV) acute GVHD (60-80%) in patients receiving a CD3 þ cell dose of approximately 1 × 10 6 /kg when post-transplant cyclosporin alone was used for GVHD prophylaxis. Urbano-Ispizua et al (1997) recently updated the Spanish experience in 20 patients undergoing CD34 þ selected PBSC using CSA combined with prednisolone post-transplant.…”
Section: Clinical Results Of Pbpc Transplantsmentioning
confidence: 99%
“…The overall incidence and severity of acute GvHD was unexpectedly low: two patients developed no GvHD (grades 0-I), seven patients developed grade II GvHD and only one patient had grade III GvHD, this was the only patient who did not receive prophylactic CyA. It is puzzling that a recent paper has reported a relatively high incidence of acute GvHD in patients receiving HLA-identical marrow or peripheral blood or both, after CD34-positive selection, despite the use of CyA and methotrexate for GvHD prophylaxis (Link et al, 1996). In that series of 10 patients the only manipulation was a Ceprate column which apparently produced a greater number of residual T cells compared to our experience: the median number of infused CD3 þ cells was 1 .…”
Section: Discussionmentioning
confidence: 96%
“…5 × 10 6 /kg CD3 þ cells. It is unclear whether this difference may have been responsible for the increased incidence and severity of acute GvHD, since Link et al (1996) were dealing with HLA-matched grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, CD14 þ monocytes or CD34 þ cells stimulated with specific cytokines in vitro differentiate into DCs (Caux et al, 1992). In contrast to humans and other primates in which long-term HSCs express CD34, murine long-term HSCs have been described as CD34 À and short-term HSCs as CD34 þ cells (Link et al, 1996;Osawa et al, 1996). Transgenic studies showed that human CD34 transgene is expressed in long-term murine CD34 À and CD34 low HSCs (Okuno et al, 2002).…”
Section: Introductionmentioning
confidence: 99%